A case of double coronary perforations and tamponade during left main percutaneous coronary intervention and treatment with stenting and autotransfusion - Gökhan Alıcı; Birol Özkan; Ali Metin Esen (KARE Publishing, 2013)
Coronary perforation is a rare complication of percutaneous coronary intervention. A 60-year-old male patient with a diagnosis of hepatocellular carcinoma was admitted to our hospital with crescendo anginal attacks. Coronary angiogram revealed significant stenosis in distal left main coronary artery (LMCA). After implanting a 4.0×18 mm coronary stent from LMCA to left anterior descending artery (LAD), coronary angiography showed a perforation in the proximal part of the LAD and a plaque shift to the osteum of circumflex artery (Cx), causing 60% stenosis. Rupture was sealed by implantation of a polytetrafluoroethylene (PTFE) coated stent in proximal LAD. Due to ongoing chest pain and electrocardiographic ischemic changes, a 3.5×18 mm coronary stent was implanted in Cx. Unfortunately, another perforation occurred in Cx. The PTFE coated stent was not flexible enough to advance from the former LMCA to LAD stent to the Cx artery, and another 3.5×18 mm coronary stent was deployed in Cx artery successfully. Although control angiography showed complete sealing of the rupture, echocardiography showed a large pericardial effusion compressing the right side of the heart. Autotransfusion was done to stabilize the hemodynamic status. One-week later, coronary angiography did not show any contrast agent extravasation. In this case, we present double coronary perforations of the LAD and Cx arteries, and successful treatment with both covered and conventional stents and autotransfusion.